Determinants of ApoB, ApoA1, and the ApoB/ApoA1 ratio in healthy schoolgirls, prospectively studied from mean ages 10 to 19 years: the Cincinnati National Growth and Health Study - Morrison, John A. (2012)
The objectives were to prospectively assess determinants of apolipoproteins B (ApoB), A1 (ApoA1), and the ApoB/ApoA1 ratio in 797 healthy black and white schoolgirls from mean ages 10 to 19. There was prospective 9-year follow-up, with measures of ApoB at mean ages 10, 12, 14,16 and 19, ApoA1at mean ages 12, 14, 16, and 19, and assessment of annual reports of delayed menstrual cyclicity (≥42 days) from ages 14 to 19. Studies of 402 black and 395 white healthy schoolgirls were done in public and private schools, in urban and suburban Cincinnati. Black girls had lower ApoB, higher ApoA1, and lower ApoB/ApoA1. SHBG at age 14 in white and black girls was inversely correlated with the ApoB/ApoA1. At age 19, ≥3 annual reports of menstrual delay ≥42 days and metabolic syndrome were associated with higher ApoB and a higher ApoB/ApoA1 ratio. From ages 14 to 19, BMI and TG were independently positively associated with ApoB. Menstrual cyclicity ≥42 days, metabolic syndrome, BMI, and TG were independently positively associated with ApoB/ApoA1 ratios, while black race was negatively associated. The atherogenic ApoB/ApoA1 ratio from ages 14 to 19 is lower in black girls, and positively associated with hyperandrogenism, menstrual cyclicity ≥42 days, BMI, TG, and the metabolic syndrome, facilitating an adolescent approach to primary prevention of cardiovascular disease.